Implementasi Model Blended Learning Pada Pembelajaran Matematika Berbasis Kurikulum Merdeka - Lisanul Uswah Sadieda; Bambang Wahyudi; Rere Dwi Kirana; Syarifah Kamaliyyah; Virda Arsyavina (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2022)
This study aims to describe the planning, implementation, learning outcomes, and responses of students in the process of learning mathematics using Blended Learning based on the Merdeka Curriculum. This research is a case study research with a qualitative and quantitative approach. The research subjects were 36 of 10th-grade students at SMAN 3 Sidoarjo as one of the Sekolah Penggerak in East Java. Data collection techniques using documentation, interviews, observations, tests, and questionnaires. The results showed that the implementation of Blended Learning at the planning stage was in the very good category, the implementation stage was in the very good category, student learning outcomes were in the sufficient category, and student responses were in the high category.